An intelligent blockchain-based system for safe vaccine supply and supervision. (June 2020) - Yong, Binbin; Shen, Jun; Liu, Xin; Li, Fucun; Chen, Huaming; Zhou, Qingguo
Highlights: A detailed vaccine blockchain system is designed for Vaccine Supply and Supervision. Machine learning based intelligent recommendation modules for vaccine management are designed and tested. Smart contracts and vaccine coin are designed to query and supervise vaccine information. Abstract: Immunization is an indispensable mechanism for preventing infectious diseases in modern society, and vaccine safety is closely related to public health and national security. However, issues such as vaccine expiration and vaccine record fraud are still widespread in vaccine supply chains. Therefore, an effective management system for the supervision of vaccine supply chains is urgently required. As the next generation of core technology after the Internet, blockchain is designed to build trust mechanisms that can change current information management methods. Meanwhile, the development of machine learning technologies provides additional ways to analyze the data in information management systems. The main objective of this study is to develop a "vaccine blockchain" system based on blockchain and machine learning technologies. This vaccine blockchain system is designed to support vaccine traceability and smart contract functions, and can be used to address the problems of vaccine expiration and vaccine record fraud. Additionally, the use of machine learning models can provide valuable recommendations to immunization practitioners and recipients, allowing them to choose better immunization methods and vaccines.